Impact of delayed adjuvant therapy after surgery in p16 positive oropharyngeal cancer: a retrospective analysis - Sievert, Matti; Goncalves, Miguel; Müller, Sarina Katrin; Hecht, M.; Pflaum, A.; Grundtner, P.; Iro, H.; Gostian, A. O.; Iro, Heinrich (European Review for Medical and Pharmacological Sciences, 2020)
OBJECTIVE: This study aimed to clarify the impact of delayed adjuvant therapy on the outcome of HPV associated oropharyngeal squamous cell carcinoma (HPV-OPSCC). PATIENTS AND METHODS: A total of 157 patients with HPV-OPSCC treated by surgery and adjuvant radiotherapy or chemoradiation therapy were analyzed retrospectively. We divided participants into two groups implementing adjuvant therapy within or after 50 days. Primary endpoints were the rates of locoregional recurrence and distant metastases, overall survival, and disease-specific survival. RESULTS: Adjuvant treatment began within 50 days (average: 38.8 days) in 79 cases compared to 78 cases after 50 days (average: 71.5 days). Five-year overall survival was 85.7% and 87.4% (p=0.588), the rates of local and regional recurrence were 3.8% and 6.4% (p=0.455) and of distant metastases 5.1% and 9% (p=0.369) implementing adjuvant treatment within or later than 50 days, respectively. CONCLUSIONS: These results suggest that adjuvant therapy initiated later than seven weeks after primary ablative surgery may still be effective HPV-OPSCC.
CRIS-Team Scopus Importer:2020-03-06